Hirnantia Fauna from the Condroz Inlier, Belgium: another case of a relict Ordovician shelly fauna in the Silurian?. (November 2021) - Pereira, Sofia; Colmenar, Jorge; Mortier, Jan; Vanmeirhaeghe, Jan; Verniers, Jacques; Štorch, Petr; Harper, David Alexander Taylor; Gutiérrez-Marco, Juan Carlos
Abstract: The end-Ordovician mass extinction, linked to a major glaciation, led to deep changes in Hirnantian–Rhuddanian biotas. The Hirnantia Fauna, the first of two Hirnantian survival brachiopod-dominated communities, characterizes the lower–mid Hirnantian deposits globally, and its distribution is essential to understand how the extinction took place. In this paper, we describe, illustrate, and discuss the first macrofossiliferous Hirnantia Fauna assemblage from Belgium, occurring in the Tihange Member of the Fosses Formation at Tihange (Huy), within the Central Condroz Inlier. Six fossiliferous beds have yielded a low-diversity, brachiopod-dominated association. In addition to the brachiopods ( Eostropheodonta hirnantensis, Plectothyrella crassicosta, Hirnantia sp., and Trucizetina ? sp.), one trilobite ( Mucronaspis sp.), four pelmatozoans ( Xenocrinus sp., Cyclocharax [col.] paucicrenulatus, Conspectocrinus [col.] celticus, and Pentagonocyclicus [col.] sp.), three graptolites ( Cystograptus ancestralis, Normalograptus normalis, and ? Metabolograptus sp.), together with indeterminate machaeridians and bryozoans were identified. The graptolite assemblage, from the Akidograptus ascensus - Parakidograptus acuminatus Biozone, indicates an early Rhuddanian (Silurian) age, and thus, an unexpectedly late occurrence of a typical Hirnantia Fauna. This Belgian association may represent an additional example of relict Hirnantia Fauna in the Silurian, sharing characteristics with the only other known from Rhuddanian rocks at Yewdale Beck (Lake District, England), although reworking has not been completely ruled out. The survival of these Hirnantian taxa into the Silurian might be linked to delayed post-glacial effects of rising temperature and sea-level, which may have favored the establishment of refugia in these two particular regions that were paleogeographically close during the Late Ordovician–early Silurian.